Analisa beban static pada tabung Apar tepung biji durian menggunakan Metode CAE (Computer Aided Engineering) - Harahap, Roby Alfiah; Siregar, Chandra Amirsyah Putra (Program Studi Teknik mesin, Fakultas Teknik, Universitas Al Azhar Medan, 2023)
With the increasing science of technology, especially in the industrial world, currently experiencing increasingly rapid progress will bring consequences and influences to the continued need for various tools to facilitate and expedite work in various fields both as complements and main products. This is what drives us to design, build and analyze an APAR (Light Fire Extinguisher) using the basic ingredients of durian seed flour and Nitrogen (N). The material used in making this apar is carbon steel with a length of 530 mm, diameter: 150 mm and tube thickness of 6 mm. Because of the static fluid in the apar, the analysis carried out is load static analysis on durian seed flour apar tubes using the CAE (Computer Aided Engineering) method, which includes stress, strain and changes in shape / displacement on each element of the durian seed flour fire extinghuisher tube with normal pressure variables of at least 16 bar and a maximum of 18 bar. The results of this analysis showed a stress of 0.607 N/m and experienced an ESTRN strain of 2.817e – 06 then underwent a change in shape / displacement of 1,000e – 30 mm at a normal pressure variable of at least 16 bar. Then with a normal pressure variable of a maximum of 18 bar get a stress result of 0.545 N/m and experience an ESTRN strain of 2.817e – 06 then experience a change in shape / displacement of 1,000-30 mm.